Leadership development for a transformational future : the vertical edge - Boysen-Rotelli, Sheila (Routledge, 2025)
An essential resource for leaders seeking to thrive in ambiguity, this book explores the pressing need for vertical leadership development in a world defined by rapid change, digital revolution, and complexity.Traditional horizontal leadership development focuses on skills but falls short in helping leaders navigate complexity, ambiguity, and exponential technological advances. What's needed now is vertical development that emphasizes expanding leaders' capacity to think strategically, manage complexity, and lead with empathy. This book bridges the gap between traditional leadership development and modern demands by providing practical tools for vertical development and, uniquely, integrating digital coaching platforms. Backed by case studies and insights from global leaders who have successfully applied vertical development, it offers actionable frameworks and strategies and introduces AI-driven coaching solutions to enhance leadership growth.Ideal for senior executives, leadership coaches, HR professionals, organizational consultants, and postgraduate leadership students, this book will help readers cultivate the mindset and skills necessary to succeed in a complex and rapidly changing world.
Keywords: Leadership.; elektronické knihy; electronic books